The cell phone vibration test: A telemedicine substitute for the tuning fork test. Issue 5 (25th September 2021) - Yang, Alex; Lewis, Robert J.; Watson, Nora; Riley, Charles A.; Tolisano, Anthony M.
Abstract: Objective: An at home‐test for differentiating between conductive and sensorineural hearing loss remains elusive. Our goal was to validate the novel cell‐phone vibration test (CPVT) against the Weber tuning fork test (WTFT) and to assess if the CPVT can be self‐administered by patients reliably. Study design: Cross‐sectional. Methods: The CPVT involves placement of a vibrating cellphone on the center of the forehead to determine which ear perceives the sound louder. 40 consecutive adult patients with an audiogram within 6 months and no report of recent hearing changes were recruited. Group 1 consisted of 20 patients who were examined by the provider with the CPVT and WTFT using various tuning forks (256, 512, and 1024 Hz). Group 2 consisted of an additional 20 patients who received instructions on self‐administering the CPVT. Kappa statistics were calculated to assess the strength of concordance between the CPVT, WTFT, and audiometric findings for group 1 and between patient self‐administered and provider administered CPVT and WTFT for group 2. Results: Concordance between CPVT and WTFT in the entire cohort was substantial (Kappa coefficient: 0.81 for 256 Hz, 0.73 for 512 Hz, and 0.62 for 1024 Hz) with similar concordances between actual and expected results based on audiogram (Kappa coefficient: 0.52 for CPVT and 0.52 for WTFT). Concordance between patient‐administered and provider‐administered CPVT showed almost perfect agreement (Kappa coefficient: 0.92). Conclusions: The CPVT provides consistent results when compared to a formal WTFT and can be reliably self‐administered by patients with appropriate instructions. Level of evidence: 4 Abstract :